A Analisis Kinerja Sistem Distribusi Air Bersih Menggunakan SPSS (Studi Kasus HIPPAM Sejahtera Desa Bakung Kecamatan Kanor Kabupaten Bojonegoro) - Mushthofa, Mushthofa; Munawaroh, Siti Rohmatul; Indriani, Yulia; Faqih, Nasyiin; Roehman, Fatchur; Chandrasasi, Dian; Nastain (Jurnal Civil Engineering Study, 2024)
Water is needed for various purposes, including human consumption, agriculture, industry, and hygiene. Protection and wise management of water resources is very necessary to ensure the availability of sufficient clean water for everyone. Services for clean water needs in Bakung Village are managed by the Drinking Water Users Population Association (HIPPAM), which currently numbers approximately +- 968 house connections (SR), and a reservoir capacity of 18